PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Andriana, Denny (Jurnal Riset Akuntansi dan Keuangan, 2014)
The purpose of this research is to examine the influence of intellectual capital and its components, represented by physical capital (capital employed), human capital, and structural capital,on financial performance of mining and manufacturing companies listed in Indonesia Stock Exchange (Bursa Efek Indonesia – BEI) period of 2010 – 2012. Total population observed during this research shows 169 mining and manufacturing companies.The sample was determined by purposive sampling method and found a total of 70 samples as the research subjects. The analytical technique for the quantitaive data uses a statistical tool, i.e. multiple regression. Intellectual capital and its components were measured by Pulic Model, while financial performance uses Return on Equty (ROE) ratio. The results show that intellectual capital and human capital have negative influence, yet insignificant, impacton companies financial performance. While physical capital (capital employed) and structural capital do have positive influence but not significanton companies financial performance.